Targets, Tracers and Translation – Novel Radiopharmaceuticals Boost Nuclear Medicine - Reischl, Gerald (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This is the fourth Special Issue in Pharmaceuticals within the last six years dealing with aspects of radiopharmaceutical sciences. It demonstrates the significant interest and increasing relevance to ameliorate nuclear medicine imaging with PET or SPECT, and also radiotherapeutical procedures.Numerous targets and mechanisms have been identified and have been under investigation over the previous years, covering many fields of medical and clinical research. This development is well illustrated by the articles in the present issue, including 13 original research papers and one review, covering a broad range of actual research topics in the field of radiopharmaceutical sciences.